Constructing a brand-new advanced oxidation process system composed of MgO2 nanoparticles and MgNCN/MgO nanocomposites for organic pollutant degradation. Issue 1 (14th December 2021) - Dong, Ningning; Wu, Doudou; Ge, Lifa; Wang, Wei; Tan, Fatang; Wang, Xinyun; Qiao, Xueliang; Wong, Po Keung
Abstract : A novel advanced oxidation process (AOP) system with high adaptability and long-term oxidation ability was firstly constructed for organic pollutant degradation via a non-radical process. Abstract : A brand-new advanced oxidation process (AOP) system consisting of MgO2 nanoparticles and MgNCN/MgO nanocomposites was firstly developed for the degradation of organic pollutants. In the novel AOP system, MgO2 nanoparticles as oxidants and MgNCN/MgO nanocomposites as activators were both obtained through a simple one-step process. Batch experiments indicated that the MgO2 –MgNCN/MgO system could efficiently degrade organic pollutants in a wide pH range (4–12), and the degradation efficiency was hardly affected by common matrix species (Cl −, NO3 −, HCO3 −, SO4 2− and humic acid) and water sources. The high stability and slow-release characteristic of MgO2 endowed the AOP system with a long-term oxidation ability for continuous degradation of organic pollutants. The dominant reactive oxygen species (ROS) responsible for organic degradation was confirmed to be singlet oxygen ( 1 O2 ), which was attributed to the activation of MgO2 by the bonding effect between MgNCN and MgO in the nanocomposites. Finally, the generated ions, NH4 +, NO2 − and NO3 −, and residual solid in the degradation solution were determined, and the process of organic degradation in the MgO2 –MgNCN/MgO system was proposed. This work not only constructed a brand-new AOP system for environmental remediation, but also offered a promising strategy for continuous treatment of organic-polluted wastewater and even soil.